-5m-6=6-3m

Simple and best practice solution for -5m-6=6-3m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5m-6=6-3m equation:



-5m-6=6-3m
We move all terms to the left:
-5m-6-(6-3m)=0
We add all the numbers together, and all the variables
-5m-(-3m+6)-6=0
We get rid of parentheses
-5m+3m-6-6=0
We add all the numbers together, and all the variables
-2m-12=0
We move all terms containing m to the left, all other terms to the right
-2m=12
m=12/-2
m=-6

See similar equations:

| -2(a-2)+5(a+3)=25 | | x=9,x=-3 | | 2=3/4x+5/4 | | 4t=32;t=8 | | 6z+1/9=7z+5/9 | | −8(−8x−6)=−6x−22 | | 5c+2=-c-8 | | 2=3/4r+5/4 | | 5t=t(t-4) | | (-6z+41)+(z+55)=2(-8z+59) | | 2−4x=−36 | | -2t-6=-t | | 9x+6x=7 | | 6-6x+42+7=0 | | 1-9v=-9v+4v+9 | | y/5+4=y/4 | | 5×-3.2=z | | (-s+8)+(7s+2)=2(-6s+23) | | 6s+2-4=10 | | -3.2×5=v | | F(1/2)=2x+1 | | 4r+10=6r-6 | | 7(2+6x)=-231 | | 0.05x+0.10(15-x)=0.90 | | 8z-3=4(z-3)+9+4+z | | -6(h+3)=-36 | | 15c=-30 | | (-p+71)+(3p-59)=2(-p+86) | | 9-b=3b-7 | | (2x-3)/4+x=(2x+3)/2+8 | | 8z-3=4(2-3)+9+4z | | 6-2/5=n |

Equations solver categories